2016
DOI: 10.1186/s13014-016-0686-7
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of electron beam energy degraders for breast boost irradiation

Abstract: BackgroundFor breast cancer patients who require electron boost energies between 6 and 9 MeV, an energy degraders (ED) in the 9 MeV beamline was specially designed and manufactured to increase the skin dose of 6 MeV and to reduce the penetration depth of 9 MeV beams.MethodsWe used Monte Carlo (MC) techniques as a guide in the design of ED for use with linear accelerators. In order to satisfy percent depth dose (PDD) characteristics and dose profile uniformity in water, the shape and thickness of Lucite® ED in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…They demonstrated that the percent horn relative to the central axis decreases when size of the field entering the applicator approaches the collimation hole size and increases with growing beam energy [24]. Park et al [25] and Northey et al [26], moreover, performed numerical simulations modeling the parameters of energy degraders [25] and plastic inserts [26] that are necessary to lower the dose profile horns and reach the predetermined field homogeneity level. They found that optimally shaped additional forming samples provide control of radiation field parameters such as penetration and flatness.…”
Section: Jinst 15 C04023mentioning
confidence: 99%
“…They demonstrated that the percent horn relative to the central axis decreases when size of the field entering the applicator approaches the collimation hole size and increases with growing beam energy [24]. Park et al [25] and Northey et al [26], moreover, performed numerical simulations modeling the parameters of energy degraders [25] and plastic inserts [26] that are necessary to lower the dose profile horns and reach the predetermined field homogeneity level. They found that optimally shaped additional forming samples provide control of radiation field parameters such as penetration and flatness.…”
Section: Jinst 15 C04023mentioning
confidence: 99%